Waste stabilization pond design for wastewater treatment at Huakhua village, Xaysettha district, vientiane capital - siharath, phoummixay; Vandeexiong Tongnamavong; Somchay Vilaychaleun; Khampasith Thammathevo; Soulyphan Kannitha; Chankhachone Sonemanivong; Phaiphana Siharath; SangKhom Singharaj; Kalaphath Kounlaxay; Pathana Inthaphouthone; Youlananh Leuanglith (Sean Institute, 2024)
The objective of this study is to design on waste stabilization pond model and evaluate the treatment efficiency of system by Chemical Oxygen Demand (COD), Biochemical Oxygen Demand (BOD5), Total Kjeldahl Nitrogen (TKN), Total Suspended Solid (TSS), Temperature (T) and Turbidity, the system includes an anaerobic, facultative and maturation ponds that is used to treat waste water and water samples is collected from 4 different sites and also 3 different times of water samples, then mixed them before adding to the system, the initial concentration of T(27.3±1.93°C), pH (8.85±0.23), Turbidity (9.73±0.57 NTU), TSS (8.33±2.52 mg/l), BOD5(11.67±1.26 mg/l), COD (24.88±3.81mg/l and TKN(0.98±0.99mg/l, in addition, the experiment took 45 days to monitor the waste water in the stabilization ponds and 5 days of detention time of sampling water to test, consequently, the results revealed that, the treatment efficiency at maturation pond of effluent values of each parameter varies from 73 to 99 %, there are T (0.47%), pH (20.74%), turbidity (82.10%), TSS (79.68%), BOD5(73.88%), COD (75.27% and TKN (86.54%).